When the role fits: How firm status differentials affect corporate takeovers - Shen, Rui; Tang, Yi; Chen, Guoli (Strategic Management Journal, 2014)
This study explores the implications of interfirm status differentials for firm behaviors in corporate takeover transactions. We argue that the more the status differential between two firms is aligned with expectations of their roles embedded in the specific economic activity, the easier it is for them to agree on the appropriate means to reach consensus on the transaction. Using the empirical context of the U.S. corporate takeover market, we found that the greater the status differential between an acquirer and a target, the more positively the market reacts to both the acquirer and the target upon the announcement of the acquisition deal, the more likely it is for the deal to be completed, and the more likely the acquirer is to achieve better post‐acquisition performance . Copyright © 2013 John Wiley & Sons, Ltd.